SISTEM OTOMATISASI PEMANAS AIR MENGGUNAKAN SENSOR DHT11 BERBASIS ARDUINO UNO - Alfin Alif Syaiji; Rahmat Hidayat (Department of Computer Engineering, Universitas Wiralodra, 2023)
Heat water is part of our needs in our daily life. With its variety of uses, a tool is needed to heat the water. In this study, a system will be designed so that the heat water can turn off automatically whenever the water is boiling. The methods used will include literacy studies from previous research journals, component selection based on literacy studies, and system design. The results obtained will be in the form of division of experimental water based on the set of temperature points on programming as a benchmark. From the experimental data, it can be concluded that the relationship between the amount of water and the temperature value for the set point in the programming will affect the water produced at the end of the experiment greatly. The more the amount of water, the higher the set point must be given.